In Vitro Research Reproducibility: Keeping Up High Standards - Hirsch, Cordula; Schildknecht, Stefan (Frontiers in Pharmacology, 2019)
Concern regarding the reproducibility of observations in life science research has emerged in recent years, particularly in view of unfavorable experiences with preclinical in vivo research. The use of cell-based systems has increasingly replaced in vivo research and the application of in vitro models enjoys an ever-growing popularity. To avoid repeating past mistakes, high standards of reproducibility and reliability must be established and maintained in the field of in vitro biomedical research. Detailed guidance documenting the appropriate handling of cells has been authored but was received with quite disparate perception by different branches in biomedical research. In that regard, we intend to raise awareness of the reproducibility issue among scientists in all branches of contemporary life science research and their individual responsibility in this matter. We have herein compiled a selection of the most susceptible steps of everyday in vitro cell culture routines that have the potential to influence cell quality and recommend practices to minimize the likelihood of poor cell quality impairing reproducibility with modest investment of time and resources.